Relativist Dispositional Theories of Value - Egan, Andy (The Southern journal of philosophy, 2012)
Adopting a dispositional theory of value promises to deliver a lot of theoretical goodies. One recurring problem for dispositional theories of value, though, is a problem about nonconvergence. If being a value is being disposed to elicit response R in us, what should we say if it turns out that not everybody is disposed to have R to the same things? One horn of the problem here is a danger of the view collapsing into an error theory—of it turning out, on account of the diversity of agents' relevant dispositions, that nothing is really a value, since nothing is disposed to elicit R in everybody. Alternatively, there is a danger of an objectionable fragmentation of value, according to which there is no such thing as a value simpliciter, but only valuesme and valuesyou, valuesus and valuesthem. I advocate a de se relativist version of a dispositional theory of value. If we go for this sort of de‐se‐ified dispositional theory, we get to keep our theoretical goodies, but we avoid the problem of nonconvergence that leads to a danger of either collapse into an error theory, or else talking‐past, and a loss of common subject matter.